2009
DOI: 10.1021/cb900165y
|View full text |Cite
|
Sign up to set email alerts
|

New and Unexpected Insights into the Modulation of LuxR-Type Quorum Sensing by Cyclic Dipeptides

Abstract: Quorum sensing (QS) is under the control of N-acylated L-homoserine lactones (AHLs) and their cognate receptors (LuxR-type proteins) in Gram-negative bacteria, and plays a major role in mediating host-bacteria interactions by these species. Certain cyclic dipeptides (2,5-diketopiperazines, DKPs) have been isolated from bacteria and reported to activate or inhibit LuxRtype proteins in AHL biosensor strains, albeit at significantly higher concentrations than native lactones. These reports have prompted the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 51 publications
6
84
1
Order By: Relevance
“…Although there are different opinions on the roles of DKPs play in QS systems (Campbell et al 2009), it has also been well documented that certain DKPs were found to be capable of activating or antagonizing LuxR-based QS systems (Degrassi et al 2002;Holden et al 1999;Tommonaro et al 2012). Klose (2006) reported that L-cyclo(Pro-Phe) could stimulate the expression of major virulence factors in V. cholerae.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are different opinions on the roles of DKPs play in QS systems (Campbell et al 2009), it has also been well documented that certain DKPs were found to be capable of activating or antagonizing LuxR-based QS systems (Degrassi et al 2002;Holden et al 1999;Tommonaro et al 2012). Klose (2006) reported that L-cyclo(Pro-Phe) could stimulate the expression of major virulence factors in V. cholerae.…”
Section: Introductionmentioning
confidence: 99%
“…Since cFP had the same apparent effect on these two strains as the others, any signaling though quorum sensing would have to operate through a different signal/sensor system. The need to find the signal/sensor system cFP uses does not conflict with the finding by Campbell et al (2009) that cFP signaling works through LuxR.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclic dipeptides are also found in fungi, and produce a number of effects in animals and plants it has been suggested that they may be involved in inter-kingdom communication (Bina and Bina. 2010, Campbell et al 2009, Park et al 2006.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the population of bacteria grows a positive feedback is started. 27 The AHL molecules are composed of fatty acyl chain linked to a lactonised homoserine through an amide bond. 28 Different structures of AHLs which modulate different regulatory proteins in different bacteria are presented in Table 2.…”
Section: Gram Negative Bacteriamentioning
confidence: 99%